An Overlooked Silica Source of the Modern Oceans: Are Sandy Beaches the Key? - Fabre, Sébastien; Jeandel, Catherine; Zambardi, Thomas; Roustan, Michel; Almar, Rafaël (Frontiers in Earth Science, 2019)
Quantification of the sources and sinks of dissolved Si (DSi) in the modern oceans remains challenging. The principal sink of silicon is typically considered to be the stripping of surface DSi by diatoms, followed by biogenic particle export and sedimentation. Contrastingly, sources of DSi are generally thought to be of lithogenic origin, silicon being released to rivers or seawater by silicate weathering. Today, source and sink fluxes are balanced within large uncertainties, at ca 10.4 ± 4.2 and 14.6 ± 7.8×1012 mol.yr-1 respectively, underlining that some processes are not well constrained and possibly overlooked so far. The poor knowledge of the oceanic DSi fluxes is also illustrated by the uncertainty on the “internal cycling”/input ratio, ranging from 23 to 53 (Tréguer and De La Rocha 2013). Here, we consider the Si flux resulting from sand grain dissolution on beaches under the pressure of the intensive and continuous shaking by the waves, a potential source of oceanic DSi that is not currently considered. To quantitatively explore this idea, we first realized an experimental dissolution of quartz grains in a stirred vessel designed to simulate the sediment orbital motion induced by the waves. These experiments lead to the calculation of a solid-liquid mass-transfer coefficient directly linked to the rotation speed of the shaker. This coefficient being itself related to the energy communicated to the liquid, we could apply a Nienow relationship to calculate a mass-transfer coefficient for beach sand exposed to 1m height waves. Extrapolation of this value to the whole sandy beaches led us to conclude that this mechanism could be significant, shortening the calculated residence time of oceanic DSi by up to a factor 2. These results have implications for the biological pump, the carbon cycle and the question of silicate weathering rates, the latter being an important CO2 sink on a geological timescale.